POLICY CAPACITY AND E-GOVERNANCE: ASSESSMENT OF THE E-GOVERNMENT SERVICES OF VALENCIA CITY, BUKIDNON (Journal of Governance and Development (JGD), 2024)
The rise of electronic governance has become a dominant force shaping the future of government. This study focuses on assessing the policy capacity of e-government services in LGU-Valencia City. It explores the competencies and capabilities of the local government in delivering basic e-government services, identifies strengths and weaknesses in their implementation, and provides recommendations for improvement. The findings highlight the analytical, operational, and political capacity of LGU-Valencia City in terms of e-governance, emphasizing essential competencies such as human resources, data management, policy support, technical expertise, and training. Operational capacity themes include organizational structure, financial and infrastructure resources, technology and information systems, and policy framework. Political capacity themes encompass leadership, citizen participation, stakeholder engagement, transparency, and intergovernmental relations. The study also reveals the presence of government-to-government (G2G) e-services in Valencia City, emphasizing collaborations and partnerships among agencies. Strengths and weaknesses of different e-government types (G2B, G2C, G2E) are identified, along with challenges in citizen acceptance and the positive impact of e-governance on businesses and employee relationships. Overall, the study concludes that LGU- Valencia City demonstrates policy capacity and readiness for digital innovation. The study suggests future researchers adopt a multi- method approach, compare policy capacity across LGUs, engage stakeholders and endusers, and emphasize capacity-building. These recommendations aim to contribute to improving governance and public services by conducting relevant and rigorous studies on policy capacity and e-governance in LGUs.